2000
DOI: 10.1364/josaa.17.001388
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the performance of the Hartmann–Shack sensor in the human eye

Abstract: A description of a Hartmann-Shack sensor to measure the aberrations of the human eye is presented. We performed an analysis of the accuracy and limitations of the sensor using experimental results and computer simulations. We compared the ocular modulation transfer function obtained from simultaneously recorded double-pass and Hartmann-Shack images. The following factors affecting the sensor performance were evaluated: the statistical accuracy, the number of modes used to reconstruct the wave front, the size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
160
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(162 citation statements)
references
References 13 publications
0
160
0
2
Order By: Relevance
“…Most of these instruments are based on the HartmannShack sensor (Prieto et al, 2000;Liang et al, 1994). They generally consist of a microlens array conjugated with the eye's pupil and a camera placed at its focal plane.…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%
“…Most of these instruments are based on the HartmannShack sensor (Prieto et al, 2000;Liang et al, 1994). They generally consist of a microlens array conjugated with the eye's pupil and a camera placed at its focal plane.…”
Section: Clinical Assessment Of Retinal Image Quality In Eyes With Asmentioning
confidence: 99%
“…Given a Hartmanngram for an unknown wavefront, one may use the deviations from that reference and 0003-6935/09/0100A1-04$15.00/0 © 2009 Optical Society of America calculate the incident wavefront gradient to an accuracy dependent on the density of the lenslets. Methods for slope calculation include the classic centroid method [1,5] and the more robust Fourier demodulation [6].…”
Section: Wavefront Sensingmentioning
confidence: 99%
“…In 2008, Manzanera et al employed an HS wavefront sensor and Xe-white-light lamp to measure the LCA (440-694 nm) using an objective method. The average LCA of three subjects was smaller than 2.0 D. 15 Manzanera et al reported that almost all of the systems in use correspond to the latter group; the HS sensor 1,16,17 was standardly used, and the HS wavefront technology became the most common method for LCA measurements. In 2015, Vinas et al studied the discrepancies between the human eye's LCA using both HS wavefront sensor and psychophysics measurement methods.…”
Section: Introductionmentioning
confidence: 99%